Coffee in Contemporary Puerto Rican Artworks: Materialism in the Age of Anthropogenic Climate Change - Morse, Michaela (Tufts Archival Research Center, 2021)
This Interdisciplinary Studies Senior Honors Thesis takes a Visual and Material Studies approach to unpacking coffee as a material in contemporary Puerto Rican artworks. A methodological discussion reviews how humans have perceived the material world within Western intellectual traditions, before asserting that it is necessary today to go beyond inherited perspectives and understand all materials to be their own lively entities. In the age of anthropogenic climate change, a world-centered view of materials is required if all entities (humans included) are to flourish on this earth. Contemporary ecologically-engaged artworks are making some of the foremost contributions to the reconsideration of the material, and the established methodology of materiality is applied to analyses of the artworks My Lands are Islands (2015) and Matters in Shelter (and Place, Puerto Rico) (2018) by Gabriela Salazar, and La Jíbarita (1991-92) and Con el Mismo Amor (1999-2007) by Jan Henle. A discussion of my dried hot drinks (2019-ongoing), a coffee-based artwork by thesis writer Michaela Morse, is included as a reflection on the work of following materials, before the text expands to characterize a wider discourse of ecologically-engaged artworks taking place in contemporary art today.; In partial fulfillment of the requirements for the degree of Bachelor of Arts In Visual & Material Studies through Food Systems, the Environment and Latinx Studies (Center for Interdisciplinary Studies); Advisor: Silvia Bottinelli